2019
DOI: 10.1002/glia.23590
|View full text |Cite
|
Sign up to set email alerts
|

Early embryonic NG2 glia are exclusively gliogenic and do not generate neurons in the brain

Abstract: In the central nervous system, the type I transmembrane glycoprotein NG2 (nerve‐glia antigen 2) is only expressed by pericytes and oligodendrocyte precursor cells (OPCs). Therefore, OPCs are also termed NG2 glia. Their fate during development has been investigated systematically in several genetically modified mouse models. Consensus exists that postnatal NG2 glia are restricted to the oligodendrocyte (OL) lineage, while, at least in the forebrain, embryonic NG2 glia could also generate astrocytes. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 31 publications
3
28
0
1
Order By: Relevance
“…In addition, in PDGFRα-CreER T2 ;RosaYFP double-transgenic adult mice, a small number of YFP+ neurons could be detected in the forebrain, especially in the piriform cortex, which is the main projection target of the olfactory bulb [35]. However, another study reported that early embryonic OPCs are restricted to the OL lineage and cannot generate neurons in the cerebellum, brain stem or olfactory bulb [36]. These contradictory observations necessitate further indepth investigation in the field.…”
Section: The Development Of Oligodendrocyte Lineage Cellsmentioning
confidence: 99%
“…In addition, in PDGFRα-CreER T2 ;RosaYFP double-transgenic adult mice, a small number of YFP+ neurons could be detected in the forebrain, especially in the piriform cortex, which is the main projection target of the olfactory bulb [35]. However, another study reported that early embryonic OPCs are restricted to the OL lineage and cannot generate neurons in the cerebellum, brain stem or olfactory bulb [36]. These contradictory observations necessitate further indepth investigation in the field.…”
Section: The Development Of Oligodendrocyte Lineage Cellsmentioning
confidence: 99%
“…During development, oligodendrocyte progenitor cells (OPCs; expressing the markers PDGFRα and NG2) are first observed in the ventricular germinal zones of the brain and spinal cord at embryonic day 12.5 (E12.5) in mice (Huang, Guo, Bai, Scheller, & Kirchhoff, ; Pringle & Richardson, ; Timsit et al, ; Warf, Fok‐Seang, & Miller, ) while a second wave of these cells originate from the dorsal cord at E15.5 (Cai et al, ; Fogarty, Richardson, & Kessaris, ; Vallstedt, Klos, & Ericson, ). Ultimately, these two populations of OPCs display similar properties (Marques et al, ; Tripathi et al, ) and both differentiate to form the myelinating cell of the central nervous system (CNS), the oligodendrocyte.…”
Section: Introductionmentioning
confidence: 99%
“…This tool also allows progenitor cells to be tracked in vivo, avoiding genetic manipulation of the animals or viral injections. In our particular case, NSCs in the LV were targeted by IUE, avoiding targeting progenitor cells at other sites in which these promoters may be active, such as pericytes in the case of the NG2 promoter [34][35][36]. NG2-hyPBase-driven integration of the StarTrack mix via IUE targets those neural progenitors in the LV with an active NG2-promoter, thereby limiting the developmental spatio-temporal parameters of the study (reviewed by Shimogory and Ogawa [37]).…”
Section: Discussionmentioning
confidence: 99%